Iqbal: scholar of East and West (part three) - Abdul Razak, Mohd Abbas (2022)
Allama Iqbal was not only a great Muslim thinker and a statesman of distinguished quality; he was also a great poet and a mystic-philosopher. As a Muslim scholar during the Western era of colonization of the East, Iqbal’s intellectual ability and performance were not just meant for finding solutions to the pressing issues of any one particular group. As a poet-philosopher and a humanist, he was interested in a wide spectrum of issues that were very important for the survival of the human race as a whole.